2010
DOI: 10.1017/s0030605309990925
|View full text |Cite
|
Sign up to set email alerts
|

The importance of human–macaque folklore for conservation in Lore Lindu National Park, Sulawesi, Indonesia

Abstract: The emerging field of ethnoprimatology focuses on the conservation implications of ecological and cultural interconnections between humans and other primates. The ethnoprimatological research reported here examined how the Tonkean macaque Macaca tonkeana is situated in the folklore of villagers in Lore Lindu National Park, Sulawesi, Indonesia. Data were collected using ethnographic interview techniques. The interviews revealed that villagers envision monkeys and humans as biologically, ecologically and cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…Such integration seems intuitive when cultural traditions, i.e., knowledge, practices, and/or beliefs, align with conservation goals; for instance when traditional taboos restrict harvesting of an imperiled species (Riley 2010, Sheppard et al 2010 or serve to create temporal or spatial wildlife sanctuaries (Johannes 2002, Bhagwat 2012. In contrast, it is less clear how cultural traditions might aid conservation when they conflict with conservation.…”
Section: Introductionmentioning
confidence: 98%
“…Such integration seems intuitive when cultural traditions, i.e., knowledge, practices, and/or beliefs, align with conservation goals; for instance when traditional taboos restrict harvesting of an imperiled species (Riley 2010, Sheppard et al 2010 or serve to create temporal or spatial wildlife sanctuaries (Johannes 2002, Bhagwat 2012. In contrast, it is less clear how cultural traditions might aid conservation when they conflict with conservation.…”
Section: Introductionmentioning
confidence: 98%
“…Taboos are traditional practices known to have promising potential for enhancing sustainable resource use. Riley [51] examined how the Tonkean macaque is situated in the folklore of villagers in central Sulawesi and revealed that, for many local villagers, the folklore has resulted in a taboo preventing them from harming the macaques, despite the frequent crop-raiding behavior of the species. Sasaoka and Laumonier [17] attest that belief in the power of supernatural agencies influences plant resource management in Amani Oho.…”
Section: The Harvesting Methodsmentioning
confidence: 99%
“…Hence, the more prosperous farmers become, the fewer positive primate-conservation sentiments they hold. Similarly, Riley (2010) reported on the changing attitudes of people towards primates in Indonesia, suggesting that while traditional knowledge and beliefs, such as social taboos, are important to conservation efforts, a reliance on culture for conservation is risky as traditional values may eventually be abandoned as socioecological and economic conditions change. Despite these relatively high levels of tolerance and benign methods of preventing crop-raiding, according to the farmers, crop-raiding by Assamese macaques occurred mainly in the early morning hours.…”
Section: General Patterns Of Crop-raidingmentioning
confidence: 99%